The Effectiveness of DPRD's Role in Enhancing Public Financial Management Accountability Through Budget Oversight: A Conceptual Framework and Survey - Taridi, Ahmad; Marantika, Abshor; Kasmawati, Kasmawati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the effectiveness of the Regional People’s Representative Council (DPRD) of Kampar Regency in budget oversight within the framework of public financial management. The research highlights the gap between the ideal role of legislative oversight and its practical implementation, particularly in relation to the follow-up of audit recommendations by the Audit Board of Indonesia. A mixed-method approach was employed, combining quantitative descriptive analysis of the Regional Budget realization and BPK recommendations during 2022–2024, with qualitative analysis through document review and interviews. The findings indicate that although Kampar Regency consistently received an Unqualified Opinion (WTP) on its financial statements, budget realization still shows deviations, especially in capital expenditures which remain low compared to the dominance of personnel expenditures. The follow-up progress of BPK recommendations reached approximately 69% by mid-2025, yet the contribution of DPRD in accelerating compliance is not well-documented quantitatively. The study concludes that DPRD’s oversight plays an important role, but its effectiveness remains constrained by technical capacity, data accessibility, and local political dynamics. The novelty of this research lies in its integrative framework that combines budget realization analysis, audit recommendation follow-up, and legislative oversight evaluation—an approach rarely applied in empirical studies in Indonesia.